INTERVENSI MODIFIKASI PERILAKU PADA ANAK YANG MENGALAMI GANGGUAN SIKAP MENENTANG DENGAN KONDISI KELUARGA YANG DISFUNGSIONAL - Lutfia Fausta Azzara; Alfi Purnamasari (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
A dysfunctional family is one of the factors that can trigger children to experience defiant behavior disorders. This disorder is characterized by defiant behavior, disobedience to orders, and provocative behavior. The purpose of this study was to determine the success of behavior modification interventions in children with behavioral disorders of defiance with dysfunctional family conditions. This study uses a quantitative approach with an experimental method using a single case pre test post test design. The participant of this research is one child who is 12 years old and has a behavior disorder of defiance. The assessment techniques used in this study were observation, interviews, and psychological test tools to assist researchers in writing a description of psychological dynamics. Researchers used behavior modification interventions to overcome defiant behavior disorders in children, the intervention was given in 3 sessions with a duration of approximately 60 minutes. The results of this study indicate that behavior modification interventions are appropriate for children who experience defiant behavior disorder with dysfunctional family conditions